Simulasi Pembelajaran IPA Menggunakan Computer Based Instruction MI Ma’arif Darussalam Plaosan - Abroto; Seka Andrean (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2021)
Learning Natural Sciences (IPA) which is often considered difficult in the learning process takes place, that is, just sitting and listening to the material from the teacher through the lecture method so that students are passive in the process of implementing the learning process. So the purpose of writing this article is to find out the implementation of science learning using Computer Based Instruction through a simulation model. This research uses qualitative research with descriptive analysis method. While in this study using data collection techniques, namely using interviews and documentation. The results showed that at MI Ma'arif Darussalam Plaosan had implemented science learning using Computer Based Instruction through a simulation model with visual media where in the learning process itself the teacher gave concrete or real examples by displaying pictures related to learning when learning. take place. The response and enthusiasm of students is more active. In the simulation model there are role models, namely: explaining, intermediary, mentoring and learning while the learning model is the simulation model itself in four stages which are orientation, training, simulation and debriefing stages